2017
DOI: 10.1007/s10456-017-9579-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-culture in endothelial growth medium enhances the angiogenic properties of adipose-derived stem/stromal cells

Abstract: Considerable progress has been made on the development of adipose-derived stem/stromal cells (ASCs) as pro-angiogenic therapeutic tools. However, variable clinical results highlight the need for devising strategies to enhance their therapeutic efficacy. Since ASCs proliferate and stabilize newly formed vessels during the angiogenic phase of adipose tissue formation, we hypothesized that mimicking an angiogenic milieu during culture of ASCs would enhance their capacity to support endothelial cell survival and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 21 publications
5
29
0
Order By: Relevance
“…In rectal cancer (Li et al 2017), aberrant mitochondrial fission mediates cellular oxidative stress that blunts cancer migration. In the present study, our results indicated that mitochondrial fission was associated with mitochondrial apoptosis and mitochondrial ROS overproduction (Koopman et al 2017;Zhou et al 2017d); inhibition of mitochondrial fission sustained mitochondrial metabolism and attenuated mitochondrial damage, finally promoting cancer cell survival (Souza et al 2018). Therefore, our results combined with those of previous studies lay the foundation for understanding the molecular features of mitochondrial fission in mitochondrial damage and substantiate the sufficiency and necessity of mitochondrial fission in inducing cancer death (Koentges et al 2017;Reddy et al 2018).…”
Section: Discussionsupporting
confidence: 78%
“…In rectal cancer (Li et al 2017), aberrant mitochondrial fission mediates cellular oxidative stress that blunts cancer migration. In the present study, our results indicated that mitochondrial fission was associated with mitochondrial apoptosis and mitochondrial ROS overproduction (Koopman et al 2017;Zhou et al 2017d); inhibition of mitochondrial fission sustained mitochondrial metabolism and attenuated mitochondrial damage, finally promoting cancer cell survival (Souza et al 2018). Therefore, our results combined with those of previous studies lay the foundation for understanding the molecular features of mitochondrial fission in mitochondrial damage and substantiate the sufficiency and necessity of mitochondrial fission in inducing cancer death (Koentges et al 2017;Reddy et al 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Capillary‐like networks are defined as a homogeneous web or dense region of endothelial cells. The VAT‐2S ASC/HUVEC spheroids co‐cultured in EGM presented capillary‐like structures, in line with previous studies, showing that the endothelial cells were stimulated to proliferate and formed capillary‐like structures (Borges et al, 2003; Frerich et al, 2008; Kang et al, 2009; Souza et al, 2018). Conversely, the VAT‐2S spheroids co‐cultured in 1:1 EGM/ADM showed only successful adipogenic differentiation but did not present prevascular structures.…”
Section: Discussionsupporting
confidence: 88%
“…Our research emphasis was that the underlying role of VEGF‐Ang‐1‐PLA nano‐sustained release microspheres on ADSC proliferation and differentiation toward ECs. It was reported that pre‐culture in endothelial growth medium enhanced the angiogenic properties of ADSCs (Souza et al, ), and Sophia Khan found that the two vital angiogenesis factors FGF and VEGF played critical roles in endotheliogenesis from human ADSCs (Khan et al, ). The present study VEGF‐Ang‐1‐PLA microspheres facilitated HGF secretion to promote ADSC proliferation and enhance CD31 + cells, but scarcely influenced the expression levels of VEGF and Ang‐1.…”
Section: Discussionmentioning
confidence: 99%